Conformation of Reconstituted Mononucleosomes and Effect of Linker Histone H1 Binding Studied by Scanning Force Microscopy - Kepert, Jochen Felix (Biophysical Society, 2003)
The conformation of mononucleosome complexes reconstituted with recombinant core histones on a 614-basepair-long DNA fragment containing the Xenopus borealis 5S rRNA nucleosome positioning sequence was studied by scanning/atomic force microscopy in the absence or presence of linker histone H1. Imaging without prior fixation was conducted with air-dried samples and with mononucleosomes that were injected directly into the scanning force microscopy fluid cell and visualized in buffer. From a quantitative analysis of ∼1,700 complexes, the following results were obtained: i), In the absence of H1, a preferred location of the nucleosome at the X. borealis 5S rRNA sequence in the center of the DNA was detected. From the distribution of nucleosome positions, an energy difference of binding to the 5S rRNA sequence of ΔΔG ≈ 3 kcal mol(−1) as compared to a random sequence was estimated. Upon addition of H1, a significantly reduced preference of nucleosome binding to this sequence was observed. ii), The measured entry-exit angles of the DNA at the nucleosome in the absence of H1 showed two maxima at 81 ± 29° and 136 ± 18° (air-dried samples), and 78 ± 25° and 137 ± 25° (samples imaged in buffer solution). In the presence of H1, the species with the smaller entry-exit angle was stabilized, yielding average values of 88 ± 34° for complexes in air and 85 ± 10° in buffer solution. iii), The apparent contour length of the nucleosome complexes was shortened by 34 ± 13 nm as compared to the free DNA due to wrapping of the DNA around the histone octamer complex. Considering an 11 nm diameter of the nucleosome core complex, this corresponds to a total of 145 ± 34 basepairs that are wound around the nucleosome.